2022
DOI: 10.1101/2022.04.05.487211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myosin Heavy Chain Converter Domain Mutations Drive Early-Stage Changes in Extracellular Matrix Dynamics in Hypertrophic Cardiomyopathy

Abstract: More than 60% of hypertrophic cardiomyopathy (HCM)-causing mutations are found in the gene loci encoding cardiac myosin-associated proteins including myosin heavy chain (MHC) and myosin binding protein C (MyBP-C). Moreover, patients with more than one independent HCM mutation may be at increased risk for more severe disease expression and adverse outcomes. However detailed mechanistic understanding, especially at early stages of disease progression, is limited. To identify early-stage HCM triggers, we generate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This functional assay compares variant frequencies in cardiomyocytes relative to their frequency in hiPSCs, when MYH7 is not expressed [30] and should not exert any functional effect. In line with previous examinations of single, pathogenic MYH7 missense variants [11,27], we demonstrate that multiplexed assessment of survival correctly segregates all tested P/LP variants and 3/4 VUS from Syn variants. HCM patients with pathogenic MYH7 variants can develop enhanced cardiac fibrosis by an unknown mechanism [29]; our data suggests that cardiomyocyte loss could play a role in the development of cardiac fibrosis by skewing cellular proportions toward fibroblasts (which do not express MYH7).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This functional assay compares variant frequencies in cardiomyocytes relative to their frequency in hiPSCs, when MYH7 is not expressed [30] and should not exert any functional effect. In line with previous examinations of single, pathogenic MYH7 missense variants [11,27], we demonstrate that multiplexed assessment of survival correctly segregates all tested P/LP variants and 3/4 VUS from Syn variants. HCM patients with pathogenic MYH7 variants can develop enhanced cardiac fibrosis by an unknown mechanism [29]; our data suggests that cardiomyocyte loss could play a role in the development of cardiac fibrosis by skewing cellular proportions toward fibroblasts (which do not express MYH7).…”
Section: Discussionsupporting
confidence: 88%
“…Pathogenic variants in many genes can disrupt protein stability and reduce abundance [24][25][26], thus, we optimized a FACS-based assay to simultaneously measure MHC-β abundance from the pooled library of MYH7 missense variant hiPSC-CMs. In addition, our lab [27] and others [11] have shown that pathogenic MYH7 variant hiPSC-CMs have reduced survival relative to synonymous controls. We find that both the multiplexed assessment of MHC-β abundance and survival in the MYH7 variant library hiPSC-CMs correctly segregated all tested pathogenic/likely pathogenic (3/3) and synonymous (3/3) variants, providing functional variant effect data for 68 amino acid substitutions.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations